Determination of factors affecting the color and reducing sugar content of sugar cane panela (Saccharum officinarum L.) - Montaña, Román; Roco-Videla, Ángel; Nieves, Ana; Flores, Sergio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The objective of this study was to determine the factors that affect the color and reducing sugar content of sugar cane (Saccharum officinarum L.), fundamental factors in the quality and marketing of product that must be evaluated and that will allow the improvement of the artisanal production of sugar cane panela. For this purpose, the MY5514 variety harvested at optimum maturity time was used and a 24 factorial design was applied to evaluate the incidence of the factors: ºBrix, purity (%), lime concentration (g.L-1) and baking temperature (ºC), on the response variables: "color" and "reducing sugar content (%)", under a completely randomized design with three replications. It was found that the significant factors for the response variable "color" for the three coordinates evaluated were: lime concentration (g.L-1), cooking temperature (ºC) and purity content (%) for the L* coordinate; ºBrix for the a* coordinate and purity content (%) for the b* coordinate. With respect to the response variable "reducing sugars (%)", the factors that significantly affected were cooking temperature (ºC) and purity content (%). It is recommended to use any of the combinations of these two factors, except the combination of 110 ºC and 95% purity, because generates a final product with commercial characteristics not desired by the consumer.